Analisis Perbandingan User Experience (UX) Pada Aplikasi Netflix Dengan Disney+ Hotstar Menggunakan Metode User Experience Questionnaire (UEQ) - Adam Huda Nugraha (Jurnal Penelitian Teknologi Informasi dan Sains, 2024)
During the COVID-19 pandemic, the Indonesian government implemented measures to ensure that the people remained in their homes and did not leave without cause. This leads to dissatisfaction among the community. More and more of them spend their time using technology like games, TV, and the internet. Internet technology has significantly changed daily life, particularly in terms of information access. Online video streaming, such Netflix and Disney+ Hotstar, is becoming the primary choice for consumers. The purpose of this study is to compare user experience (user satisfaction) between the Netflix and Disney+ Hotstar apps using the User Experience Questionnaire method (UEQ). Data collection is carried out using Google Forms as a medium to get user feedback through provided questions. Data analysis is done using Data Analysis Tools (DAT). The research results show that 5 out of 6 scales (Attractiveness, Clarity, Efficiency, Accuracy, and Novelty) for the Netflix application received an assessment of ‘Above average,’ while the Stimulation and Efficiency scales received a rating of ‘Good.’ On the other hand, for the Disney+ Hotstar application, 4 out of 6 scales (Attractiveness, Clarity, Efficiency, Accuracy, and Novelty) received a rating of '.